Overview on the different type of composite materials for footwear application - Marsi, Noraini; Thana Singam, Rupashinii; Mohd Rus, Anika Zafiah; Zulkipli, Muhammad; Hehsan, Haffidzudin; Nawawi, Azli (Penerbit UTHM, 2020)
In 2010, an overview on Malaysian footwear industry that obtained source form Department of Statistics Malaysia (DOSM), the import and export of footwear consist of shoe pad has reached RM 43.99 million and RM 17.04 million in the year 2009.